MODEL PENYADARAN ORANGTUA MENGGUNAKAN PENDEKATAN INTERAKSI DALAM UPAYA MEMINIMALISIR TERJADINYA KEKERASAN PADA ANAK. - Febritesna Nuraini (Khazanah Pendidikan, 2016)
Violence can happen to anyone, regardless of age regardless of economic status, educational background, religion and ethnicity. Cases of violence are increasing from year to year. Victims of violence not only women but children under the age of the victims. Violence occurs not only home environment, schools and places of common violence. The family is the first educational place for children, after school and community environments. Education is most important is the interaction between parent and child. The purpose of this study was to determine the factors that influence violence in schools and homes as the system of organization, this study was parental awareness of how to model for a parent or child. Kata kunci : Model awareness, parents and children.